6′-Sialyllactose Alleviates Muscle Fatigue through Reduced Blood Lactate Level after Treadmill Exercise in Mice - Park, Eun-Jung; Kim, Li-La; Lee, Jie-Oh; Lee, Hay-Young; Kim, Yong-An; Go, Hiroe (Nutrients, 2024)
6′-Sialyllactose (6′-SL), found in human breast milk, exhibits anti-inflammatory, immune function-enhancing, brain development-promoting, and gut health-improving effects. However, its effects on muscle fatigue remain unknown. Here, we aimed to investigate the effects of 6′-SL on blood lactate level, muscle fiber type, and oxidative phosphorylation protein complexes (OXPHOS) in muscle after exercise using C57BL/6J male mice. C57BL/6J mice were randomly assigned to control or 100 mg/kg 6′-SL. After 12 weeks of 6′-SL administration, the mice were made to perform treadmill exercise; their blood lactate and glucose levels were measured at the basal level (rest) and 0, 5, and 10 min after treadmill exercise. Results showed that 6′-SL treatment in C57BL/6J mice significantly reduced blood lactate level and improved blood glucose level. Moreover, 6′-SL increased the expression of slow-myosin heavy chain (MHC) and OXPHOS in gastrocnemius muscle. In addition, 6′-SL treatment for 12 weeks did not affect food intake, serum biomarkers of tissue injury, and lipid profiles compared with those of the controls. These findings indicate that non-toxic 6′-SL suppressed muscle fatigue during exercise by promoting protein expression of muscle fibers, especially slow-twitch muscle fibers characterized by abundant OXPHOS complexes and decreased blood lactate level. This study suggests that 6′-SL holds promise as a nutritional supplement in exercise and clinical settings, subject to further validation.